The Implementation of the Murabahah Agreement in MSME Financing at KSPPS Mitra Mandiri Wonogiri - Ilham Hendrawan (Council: Education Journal of Social Studies, 2025)
This study aims to analyze the implementation of the murabahah contract in funding MSMEs (Micro, Small, and Medium Enterprises) at KSPPS Mitra Mandiri Wonogiri. Using qualitative methods, with in-depth interviews with KSPPS Mitra Mandiri Wonogiri. This study shows that KSPPS Mitra Mandiri has successfully implemented the murabahah contract. However, there are several challenges faced, such as the lack of understanding of members about the murabahah contract. With the need for education for members of KSPPS Mitra Mandiri Wonogiri regarding the murabahah contract. This study analyzes KSPPS Mitra Mandiri Wonogiri in carrying out the murabahah contract and compiling transparent procedures in determining the resale price to members, so that there is no misunderstanding from KPPS Mitra Mandiri Wonogiri and members